Subnanometric osmium clusters confined on palladium metallenes for enhanced hydrogen evolution and oxygen reduction catalysis - Prabhu, P. (2024)
Highly efficient, cost-effective, and durable electrocatalysts, capable of accelerating sluggish reaction kinetics and attaining high performance, are essential for developing sustainable energy technologies but remain a great challenge. Here, we leverage a facile heterostructure design strategy to construct atomically thin Os@Pd metallenes, with atomic-scale Os nanoclusters of varying geometries confined on the surface layer of the Pd lattice, which exhibit excellent bifunctional properties for catalyzing both hydrogen evolution (HER) and oxygen reduction reactions (ORR). Importantly, Os5%@Pd metallenes manifest a low η10 overpotential of only 11 mV in 1.0 M KOH electrolyte (HER) as well as a highly positive E1/2 potential of 0.92 V in 0.1 M KOH (ORR), along with superior mass activities and electrochemical durability. Theoretical investigations reveal that the strong electron redistribution between Os and Pd elements renders a precise fine-tuning of respective d-band centers, thereby guiding adsorption of hydrogen and oxygen intermediates with an appropriate binding energy for the optimal HER and ORR.